Sosialisasi Pemanfaatan Kulit Mangrove Sebagai Pewarna Alami Ecoprint Teknik Steam Pounding di Bintan Buyu: Penelitian - Isheka Yuli Naisa; Nur Destiana; Novira Dwi Ayu Ningtias; Yunita; Sudirman Putra Sirimai; Zul Akmal Mursyam; Daniel Frans Lego Panggabean; Galuh Dea Tiara Shandy; Zeldiyan Arafat; Chindy Marselina (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The increase in synthetic dye waste from the textile industry causes significant environmental pollution, prompting the need for environmentally friendly dye alternatives. One potential source is the bark of the Rhizophora mucronata mangrove tree, which is rich in tannins and phenolic compounds. This article describes the socialization and training activities on the use of mangrove bark as a natural dye in ecoprinting with an innovative combination of pounding and steaming techniques in Bintan Buyu Village, Bintan Regency, Riau Islands. The implementation methods included socialization on the basic concepts of ecoprinting, introduction to the ecological and economic potential of mangroves, and practical training on ecoprinting. The training process included mordanting fabric with alum, basic dyeing using mangrove bark decoction, leaf printing (pounding), and color fixing (steaming). The pounding technique produced clear and detailed leaf motifs, while the steaming technique increased color fastness to prevent fading. The results of the activity showed high enthusiasm among participants, as seen from their active participation in discussions, practice, and the quality of the works produced. The participants' ecoprint products featured a combination of natural brown colors with sharp and aesthetic patterns of various leaves. This activity succeeded in increasing the community's knowledge, skills, and awareness of the sustainable use of local resources. The combined pounding– steam technique has proven effective in creating environmentally friendly ecoprints with good pattern quality and color fastness, while also opening up opportunities for creative businesses based on the potential of local mangroves.